The extracellular matrix glycoprotein fibrillin-1 in health and disease - Li, Li; Huang, Junxin; Liu, Youhua (Frontiers in Cell and Developmental Biology, 2024)
Fibrillin-1 (FBN1) is a large, cysteine-rich, calcium binding extracellular matrix (ECM) glycoprotein encoded by FBN1 gene. It serves as a structural component of microfibrils and provides forcebearing mechanical support in elastic and nonelastic connective tissue. As such, mutations in the FBN1 gene can cause a wide variety of genetic diseases such as Marfan syndrome, an autosomal dominant disorder characterized by ocular, skeletal and cardiovascular abnormalities. FBN1 also interacts with numerous microfibril-associated proteins, growth factors and cell membrane receptors, thereby mediating a wide range of biological processes such as cell survival, proliferation, migration and differentiation. Dysregulation of FBN1 is involved in the pathogenesis of many human diseases, such as cancers, cardiovascular disorders and kidney diseases. Paradoxically, both depletion and overexpression of FBN1 upregulate the bioavailability and signal transduction of TGF-β via distinct mechanisms in different settings. In this review, we summarize the structure and expression of FBN1 and present our current understanding of the functional role of FBN1 in various human diseases. This knowledge will allow to develop better strategies for therapeutic intervention of FBN1 related diseases.